Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan pada CV. Eagle Machinery Indonesia, Tangerang: budaya organisasi, motivasi kerja, kepuasan kerja - Kamsidik, Kamsidik; Krisnaldy, Krisnaldy; Indrayadi, Rachmat (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research aims to analyze the partial influence of organizational culture and work motivation on job satisfaction at CV. Eagle Machinery Indonesia, Tangerang. The study also examines the simultaneous impact of both organizational culture and work motivation on job satisfaction. The research adopts an associative approach with a quantitative method, involving a population of 125 respondents and a sample of 96 respondents determined using the Slovin formula. Data were collected through questionnaires, and data analysis techniques included validity and reliability tests, classical assumption tests, multiple regression analysis, and hypothesis testing using t-tests, f-tests, and coefficient of determination. The findings reveal that organizational culture has a significant partial effect on job satisfaction, as does work motivation. Furthermore, organizational culture and work motivation simultaneously influence job satisfaction. The results indicate that organizational culture and work motivation contribute 74.9% to job satisfaction, with the remaining 25.1% influenced by other factors. Based on these findings, it is recommended that the company enhances job satisfaction by improving strategies related to organizational culture and work motivation for its employees. This study underscores the importance of fostering a positive organizational culture and motivation to improve overall employee satisfaction at CV. Eagle Machinery Indonesia.